Inferences on the evolutionary history of the S-element family of Drosophila melanogaster. - Maside, X.; Bartolome, C.; Charlesworth, B. (Molecular Biology and Evolution, 2003)
The S-element family of transposable elements has been characterized in D. melanogaster. Attempts to find it in other Drosophila-related species have failed, suggesting that this element family may have recently invaded the D. melanogaster genome by horizontal transfer. In order to investigate its evolutionary history, we analyzed the patterns of DNA polymorphism among the S-element copies present in a sample genome (Drosophila Genome Project). The observed levels of nucleotide diversity are significantly lower than theoretical expectations based on the neutral model. This is consistent with evidence for ongoing gene conversion among copies and for purifying selection on the elements' sequences, particularly on the terminal inverted repeats. A phylogenetic analysis revealed that the members of the S-element family can be grouped into at least two genetically differentiated clusters. The level of divergence between these clusters suggests that the S elements invaded the genome of the ancestor of D. melanogaster before the speciation of the D. melanogaster complex. However, other relevant scenarios are also discussed.